Pengaruh Lingkungan Kerja dan Stres Kerja terhadap Disiplin Kerja pada Komite Nasional Ekonomi dan Keuangan Syariah - Bimo Satrio Widianto; Irwin Sukrisno Soegeng; Andri Rizko Yulianto (Ikatan Da'i Indonesia, 2025)
This study aims to analyze the influence of work environment and work stress on employee work discipline at the National Committee for Islamic Economics and Finance (KNEKS). Work Environment and Work Stress have an important role in work discipline. The method used is quantitative with a statistical approach. Data were collected by distributing questionnaires to 45 respondents. Data analysis used multiple linear regression tests with the help of SPSS 27 software. The results of this study are (1) the work environment has a positive but not significant influence on work discipline based on the results of the T test because the Sig value is 0.051 > 0.05 and the calculated t value is 2.011 > t table 1.682, so it can be concluded that Ho1 is accepted and Ha1 is rejected (2) Work stress has a positive and significant influence on employee performance based on the results of the T test because the Sig value is 0.000 < 0.05 and the calculated t value is 5.019 > 1.682, so it can be concluded that Ho2 is rejected Ha2 is accepted, (3) The work environment and work stress together have a positive and significant influence on work discipline.